A Role for the Cannabinoid 1 Receptor in Neuronal Differentiation of Adult Spinal Cord Progenitors in vitro is Revealed through Pharmacological Inhibition and Genetic Deletion - Sideris, Alexandra; Bekker, Tatiana; Chan, Wai Si; Montoya-Gacharna, Jose V.; Blanck, Thomas J.; Recio-Pinto, Esperanza (Frontiers in Neuroscience, 2012)
In contrast to the adult brain, the adult spinal cord is a non-neurogenic environment. Understanding how to manipulate the spinal cord environment to promote the formation of new neurons is an attractive therapeutic strategy for spinal cord injury and disease. The cannabinoid 1 receptor (CB1R) has been implicated as a modulator of neural progenitor cell proliferation and fate specification in the brain; however, no evidence exists for modulation of adult spinal cord progenitor cells. Using adult rat spinal cord primary cultures, we demonstrated that CB1R antagonism with AM251 significantly decreased the number of Nestin(+) cells, and increased the number of βIII tubulin(+) and DCX(+) cells, indicative of neuronal differentiation. AM251’s effect was blocked by co-application of the CB1R agonists, WIN 55,212-2 or ACEA. Consistent with our hypothesis, the chronic absence of CB1R via the use of knock-out (CB1-/-) mice resulted in significantly higher levels of DCX(+) cells compared to wild type (CB1+/+) cultures, indicative of enhanced neuronal differentiation in CB1-/- spinal cords. Moreover, AM251 promoted neuronal differentiation in CB1+/+, but not in CB1-/- cultures. Since CB1R modulates synaptic transmission, and synaptic transmission has been shown to influence progenitor cell fate, we evaluated whether AM251-induced neuronal differentiation was affected by chronic inactivity. Interestingly, either the presence of the voltage-dependent sodium channel blocker tetrodotoxin (TTX), or the removal of mature neurons, inhibited the AM251-induced increase in DCX (+) cells. In summary, antagonism or absence of CB1R promotes neuronal differentiation in adult spinal cord cultures, and this action appears to require TTX-sensitive neuronal activity.